VITTORIA VETRA'S SELF-CONFIDENCE IN DAN BROWN'S ANGELS AND DEMONS: Self-confidence - Syafa'atul Izzah; Novi Sriwulandari (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
Self-confidence has been operationalized through self-esteem and self-efficacy. Believing in oneself (self-esteem) and one's capabilities (self-efficacy) can motivate an individual to take on more projects or work to further reach their goals, in other words, demonstrate self-confidence. This study aims to discuss Vittoria Vetra's self-confidence in Dan Brown's novel Angels and Demons. This study focuses on three problems; Vittoria Vetra's self-confidence, the factors that influence Vittoria Vetra's self-confidence, and the impact of Vittoria Vetra's self-confidence in Dan Brown's 'Angels and Demons'. The study uses a descriptive qualitative approach to answer the problems. The main data were taken from the sentence in the novel 'Angels and Demons' by Dan Brown. To collect the data the researcher uses library research, using some books and other references, such as articles, journals, and websites related to the subject analyzed. The data was derived by close reading particularly. After being read several times, the data had been collected and selected based on the purpose of the study.